2003
DOI: 10.1021/cc030011z
|View full text |Cite
|
Sign up to set email alerts
|

Automated Parallel Solid-Phase Synthesis and Anticancer Screening of a Library of Peptide-Tethered Platinum(II) Complexes

Abstract: The automated parallel solid-phase synthesis of a 36-member library of peptide-tethered platinum(II) complexes is described. The identity and quality of each product were confirmed by mass spectrometry and (1)H NMR. Subsequently, each compound was screened for in vitro anticancer activity by treating the A2780 (human ovarian carcinoma) cell line with two concentrations of the drugs (100 and 10 microM) in quadruplicate. The reduction of cell proliferation induced by the drugs at these concentrations was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 21 publications
1
29
0
1
Order By: Relevance
“…This technology was used to screen dozens of platinum(II)-peptide conjugates in vitro for anticancer activity, although no significant hits were obtained in this screen. 174 Although these peptide conjugates exhibit a reduced capacity to platinate DNA, and consequently reduced potency, the DNA sequence specificity of platination is generally unaltered with different peptide sequences. 175 We note briefly, however, that use of individual charged amino acids, such as ornithine, lysine, or arginine, in place of the nonleaving group ligands can alter this specificity.…”
Section: Platinum(ii) Compounds With a Mechanism Of Action Similarmentioning
confidence: 99%
“…This technology was used to screen dozens of platinum(II)-peptide conjugates in vitro for anticancer activity, although no significant hits were obtained in this screen. 174 Although these peptide conjugates exhibit a reduced capacity to platinate DNA, and consequently reduced potency, the DNA sequence specificity of platination is generally unaltered with different peptide sequences. 175 We note briefly, however, that use of individual charged amino acids, such as ornithine, lysine, or arginine, in place of the nonleaving group ligands can alter this specificity.…”
Section: Platinum(ii) Compounds With a Mechanism Of Action Similarmentioning
confidence: 99%
“…3). Remarkably in other combinatorial evaluations of platinum antitumour drugs far fewer active compounds were discovered [20,21], illustrating the high potential of asymmetric cisplatin analogues.…”
Section: Resultsmentioning
confidence: 99%
“…Platinum(II) complexes with aliphatic amines as ligands (24, Scheme 13) reported by Reedijk et al are reasonably stable under acidic conditions and libraries of peptide-platinum(II) conjugates were prepared on solid phase (using a Rink amide linker [6] ) and their anticancer activity was evaluated after cleavage from the support. [25] For resinbound Pt II complexes, gel-phase 195 Pt NMR spectroscopy was found to be a very useful analytical tool for monitoring the reaction. [23] The use of 22-PS or 24-PS as starting materials for the SPS of oligonuclear metal complexes with welldefined chain lengths and end groups awaits exploration.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…The pepti- de99m Tc-chelate conjugate 8-PS has been prepared by SPPS as a potential radiopharmaceutical equipped with a targeting vector (Scheme 5). [21] Reedijk et al reported the first example of a solid-phase synthesis of peptide-tethered dichloroplatinum(II) complexes, [22][23][24] and the automated synthesis of a family of 36 analogues [25] as well as the SPPS of dinuclear lysine-bridged platinum(II) complexes (Scheme 5; 9-PS) [26] with the aim to discover new potent platinum anticancer agents. DNA-sequence selective hairpin polyamide platinum(II) complexes have also been prepared on solid supports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation